Father‐child bonding among Japanese fathers of infants: A municipal‐based study at the time of the 4‐month child health checkup. Issue 5 (27th August 2021) - Yoshida, Kazuki; Goto, Aya; Takebayashi, Yoshitake; Murakami, Michio; Sasaki, Mie
Abstract: We aimed to clarify the factor structure of a bonding measure among Japanese fathers with infants and the factors associated with the subscales. Among fathers of children attending the 4‐month health checkup, the Japanese version of the Mother‐to‐Infant Bonding Scale had a two‐factor structure comprising "anger" and "lack of affection." Anger was associated with fathers' work demands and poor mental condition, and lack of affection with fathers' older age, poor mental condition, and interpersonal problems at home. Paternal parenting support needs to account for not only the fathers themselves, but also interpersonal communication at home and in the work environment. Resumen: Nos propusimos clarificar la estructura de factores de una medida de acercamiento afectivo entre los papás japoneses con infantes y los factores asociados con las subescalas. Entre los papás de niños que asistían al chequeo de salud de 4 meses, la versión japonesa de la Escala de Acercamiento Afectivo Madre a Infante tuvo una estructura de dos factores que comprende "ira" y "falta de afecto." La "Ira" se asoció con las responsabilidades del trabajo de los papás y la débil condición mental, y la "falta de afecto" con la más vieja edad de los papás, la débil condición mental y los problemas interpersonales en casa. La crianza paterna apoya las necesidades de dar cuenta no sólo de los padres mismos, sino también de la comunicación interpersonal en casa y el ambiente de trabajo. Résumé: Notre but était de clarifier la structure de facteur d'une mesure de lien entre les pères japonais de nourrissons et les facteurs liés aux sous‐échelles. Parmi les pères d'enfants présents pour leur visite médicale de 4 mois la version japonaise de l'Echelle de Lien Mère‐Nourrisson était une structure de deux facteurs comprenant "la colère" et "le manque d'affection". "La colère" était liée aux exigences du travail des pères et à une condition mentale moins élevée, et "le manque d'attention" était lié à l'âge plus élevés des pères, à une condition mentale moins élevée et à des problèmes relationnels à la maison. Le soutien de parentage paternel a besoin d'être pris en compte non seulement pour ce qui concerne les pères eux‐mêmes mais aussi la communication relationnelle à la maison et l'environnement au travail. Zusammenfassung: Vater‐Kind‐Bindung bei japanischen Vätern von Säuglingen: Eine gemeindebasierte Studie zum Zeitpunkt einer 4‐Monats‐Kinderuntersuchung Unser Ziel war es, die Faktorenstruktur und die mit den Subskalen verbundenen Faktoren eines Maßes für Bindung bei japanischen Vätern von Kleinkindern zu untersuchen. Die japanische Version der Mutter‐Kind‐Bindungsskala hatte bei den Vätern, deren Kinder 4 Monate nach der Geburt ärztlich untersucht wurden, eine Zwei‐Faktoren‐Struktur, die "Ärger" und "Mangel an Zuneigung" umfasste. "Ärger" war mit Arbeitsanforderungen und schlechter psychischer Verfassung bei den Vätern assoziiert, während "fehlende Zuneigung" mit zunehmendem Alter und schlechter psychischer Verfassung bei den Vätern sowie zwischenmenschlichen Problemen zu Hause assoziiert war. Erziehungsunterstützung für Väter sollte nicht nur die Väter selbst, sondern auch die zwischenmenschliche Kommunikation zu Hause und das Arbeitsumfeld berücksichtigen. 抄録: 日本人の乳幼児の父親における父−子ボンディング:3−4カ月健診での地方自治体ベースの研究 本研究の目的は、日本人の乳児の父親におけるボンディング尺度の因子構造と下位尺度に関連する因子を明らかにすることである。4ヶ月健診を受けた乳児の父親に対して行ったMother‐to‐Infant Bonding Scale (MIBS) 母子絆尺度の日本語版は、「怒り」と「愛情の欠如」の2因子構造であった。「怒り」は父親の仕事の負担と不健全な精神状態に関連し、「愛情の欠如」は父親の高齢化、不健全な精神状態、家庭での対人関係の問題に関連していた。父親への育児支援においては、父親自身だけでなく、家庭や職場環境での対人コミュニケーションも考慮する必要がある。 摘要: 我们旨在阐明一次日本父亲与婴儿之间连结关系测量的因素结构, 以及与各分量表相关的因素。在四个月的儿童参加健康检查时, 其父亲在日本版的"母婴连结量表"中, 有一个由"愤怒"和"缺乏亲情"组成的双因素结构。"愤怒"与父亲的工作烦恼和不良心理状况有关, 而"缺乏亲情"与父亲年龄大、不良心理状况和家庭人际关系问题有关。父亲的育儿支持不仅要考虑父亲本身, 还要考虑家庭和工作环境中的人际沟通。 ملخص: الترابط بين الأب والطفل بين الآباء اليابانيين للرضع: دراسة محلية في وقت إجراء فحص صحة الطفل في عمر أربعة شهور استهدفت الدراسة توضيح الهيكل العامل لمقياس الترابط بين الآباء اليابانيين مع الرضع والعوامل المرتبطة بالمقاييس الفرعية. ومن بين آباء الأطفال الذين يحضرون الكشف الطبي في عمر أربعة شهور، كان للنسخة اليابانية من مقياس الترابط بين الأم والرضيع هيكل مكون من عاملين يتألف من "الغضب" و "انعدام المودة". ارتبط "الغضب" بمطالب عمل الآباء وسوء الحالة النفسية، وارتبط "نقص المودة" بتقدم الآباء في السن، وسوء الحالة النفسية والمشاكل الشخصية في المنزل. ولذلك لا يحتاج دعم التربية الأبوية إلى أن يكون مسؤولا عن الآباء أنفسهم فحسب، بل أيضا عن التواصل بين الأشخاص في المنزل وبيئة العمل.